Analysis of the Characteristics of Expressive Works of El Greco with a View to the Initial Expressionism School (1905-1920) - Jafarzadeh, Zahra; Sadri, Mina (Journal of History Culture and Art Research, 2017)
Expression of inner and different sense of individuals about various effective events would make people familiar with the concept used to describe and name art works in which, the painter applies all visual elements in a page to express his/her inner sense that is usually raised from negative feelings such as fear and anxiety. This paper aims at finding some common features such as color specifications, expression of a specific form, structure and composition analyzing such features in paintings of El Greco and compares it with painting works of Expressionism School. The result of this study confirmed some common features in works of El Greco and works of majority of artists inspired by primitive Expressionism School.